Pengaruh Panjang Serat Terhadap Kekuatan Impak Material Komposit Berpenguat Serat Lidah Mertua (Sansevieria Clyndirica) Untuk Aplikasi Spakbor Sepeda Motor - mansjur, zuldesmi; Sinaga, Amos; Rampo, Yohanis (Jurnal Mesin Nusantara, 2025)
The use of composite materials made from natural fibers is increasingly popular as an alternative to synthetic fibers that are not environmentally friendly. One type of natural fiber with great potential is snake plant fiber (Sansevieria cylindrica), which has superior mechanical characteristics and can act as a reinforcement in composites. This study aims to evaluate the impact of variations in snake plant fiber length on the impact strength of composites planned to be used as a replacement material for automatic motorcycle front fenders. The composite was made with a volume ratio of 30% fiber and 70% polyester resin, with fiber length variations of 30 mm, 50 mm, and 70 mm. Impact tests were conducted using the ASTM E23 Charpy method, and microstructural analysis was performed to understand the failure mechanism. The research findings showed that composites with 30 mm fibers provided the best impact performance with an impact energy reaching 4.22 Joules and an impact value of 0.0531 J/mm². Increasing the fiber length to 50 mm and 70 mm actually decreased the impact resistance, up to 2.84 Joules and 1.53 Joules, respectively. Compared to conventional fender material, the snake plant fiber composite exhibits significantly higher impact values. The microstructure exhibits a more uniform fiber distribution at a length of 30 mm, while longer fibers tend to cause defects such as debonding, fiber pullout, and voids. Therefore, a fiber length of 30 mm is considered optimal.